Metabolic outcomes in young children with type 1 diabetes differ between treatment centers: the Hvidoere Study in Young Children 2009 - de Beaufort, Carine E; Lange, Karin; Swift, Peter G F; Aman, Jan; Cameron, Fergus; Castano, Luis; Dorchy, Harry; Fisher, Lynda K; Hoey, Hilary; Kaprio, Eero; Kocova, Mirjana; Neu, Andreas; et al. (Wiley Online Library, 2013)
Objective To investigate whether center differences in glycemic control are present in prepubertal children <11 yr with type 1 diabetes mellitus. Research Design and Methods This cross‐sectional study involved 18 pediatric centers worldwide. All children, <11 y with a diabetes duration ≥12 months were invited to participate. Case Record Forms included information on clinical characteristics, insulin regimens, diabetic ketoacidosis (DKA), severe hypoglycemia, language difficulties, and comorbidities. Hemoglobin A1c (HbA1c) was measured centrally by liquid chromatography (DCCT aligned, range: 4.4–6.3%; IFFC: 25–45 mmol/mol). Results A total of 1133 children participated (mean age: 8.0 ± 2.1 y; females: 47.5%, mean diabetes duration: 3.8 ± 2.1 y). HbA1c (overall mean: 8.0 ± 1.0%; range: 7.3–8.9%) and severe hypoglycemia frequency (mean 21.7 events per 100 patient‐years), but not DKA, differed significantly between centers (p < 0.001 resp. p = 0.179). Language difficulties showed a negative relationship with HbA1c (8.3 ± 1.2% vs. 8.0 ± 1.0%; p = 0.036). Frequency of blood glucose monitoring demonstrated a significant but weak association with HbA1c (r = −0.17; p < 0.0001). Although significant different HbA1c levels were obtained with diverse insulin regimens (range: 7.3–8.5%; p < 0.001), center differences remained after adjusting for insulin regimen (p < 0.001). Differences between insulin regimens were no longer significant after adjusting for center effect (p = 0.199). Conclusions Center differences in metabolic outcomes are present in children <11 yr, irrespective of diabetes duration, age, or gender. The incidence of severe hypoglycemia is lower than in adolescents despite achieving better glycemic control. Insulin regimens show a significant relationship with HbA1c but do not explain center differences. Each center's effectiveness in using specific treatment strategies remains the key factor for outcome.